Arthroscopy of the Distal Radioulnar Joint - Nakamura, T.; Matsumura, N.; Iwamoto, T.; Sato, K.; Toyama, Y. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2014)
Wrist arthroscopy is now widely indicated for diagnosis and treatment of acute or chronic wrist pain, especially for triangular fibrocartilage complex (TFCC) lesions, as a gold standard. In most cases radiocarpal and midcarpal arthroscopy was performed, while DRUJ arthroscopy has been rarely performed because of its difficulties. Recent anatomic and biomechanical studies demonstrated that the radioulnar ligament (RUL), which is the proximal component of the TFCC facing to the DRUJ, is the primary stabilizer of the distal radioulnar joint (DRUJ). Rupture of the radioulnar ligament (RUL) at the fovea area, where it is the main attaching portion to the ulna and is the isometric point during forearm rotation as the rotation axis passes, is responsible for DRUJ instability. Although physical examination and imaging diagnosis may indicate a foveal detachment of the TFCC, DRUJ arthroscopy is potential for visualizing the RUL at the fovea. Role of DRUJ arthroscopy should be more important not only for diagnosis of rupture of the RUL but also for decision making of treatment option for RUL tear. DRUJ arthroscopy also demonstrates the joint surface of both the sigmoid notch and ulnar head, and the proximal surface of the TFCC.
Keywords: arthroscopy; distal radioulnar joint; DRUJ; triangular fibrocartilage complex; TFCC; radioulnar ligaments; instability